2015
DOI: 10.1164/rccm.201408-1423oc
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Measurement of Airway Remodeling and Emphysema in Advanced Chronic Obstructive Pulmonary Disease. Correlation with Pulmonary Hypertension

Abstract: This study demonstrates, for the first time to our knowledge, an association between structural alterations of bronchi and PH in COPD. Unlike quantification of emphysema, CT measurement of airway remodeling correlates with PAPm and could be used to estimate the severity of PH in COPD. Airway remodeling burden is not limited to airflow limitation in the assessment of COPD severity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 48 publications
6
61
0
1
Order By: Relevance
“…There are new parameters that may offer prognostic insight in the future, e.g., PAP m may correlate with increased airway wall thickness. Furthermore, patients with pulmonary hypertension have significantly higher pulmonary artery/ascending aorta ratios [21]. For the prediction of mortality, a normalised emphysema score was formulated in the study conducted by Gallardo-Estrella et al [22].…”
Section: Ct Quantification Of Emphysemamentioning
confidence: 99%
“…There are new parameters that may offer prognostic insight in the future, e.g., PAP m may correlate with increased airway wall thickness. Furthermore, patients with pulmonary hypertension have significantly higher pulmonary artery/ascending aorta ratios [21]. For the prediction of mortality, a normalised emphysema score was formulated in the study conducted by Gallardo-Estrella et al [22].…”
Section: Ct Quantification Of Emphysemamentioning
confidence: 99%
“…Remodeling of pulmonary arteries is not only seen in advanced COPD patients, but also in non-hypoxic mild COPD patients [28,36,39,40]. However, "muscling" in pulmonary arterioles may be frequently observed in COPD patients who have not yet developed PHT but undergone organ transplantation [41].…”
Section: Pulmonary Vascular Remodelingmentioning
confidence: 99%
“…Peinado et al [39] reported that there was an infiltration of the adventitia layer of pulmonary artery by inflammatory cells and they showed that there was a relationship with the number of inflammation cells, the expansion in the intimal layer and endothelial cell dysfunction. It was reported by Chaout et al [43] that circulating IL-6 levels were associated with the mean PAP.…”
Section: Pulmonary Vascular Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress has been made in understanding the prognostic implications of pulmonary hypertension across disease entities [1]. Advances in defining mixed pre-and post-capillary pulmonary hypertension, uncovering occult pulmonary vascular and left heart disease in the catheterisation laboratory [8,9], and understanding lung pathologic changes in pulmonary hypertension associated with parenchymal lung disease have been substantial [10][11][12]. Sorely lacking are noninvasive markers of pulmonary vascular pathology, tools to detect ongoing vascular injury versus quiescence or healing, understanding of mediators of the right heart response to haemodynamic and environmental stressors, and myocardial targets for therapy.…”
Section: Heeding the Call: The Nhlbi Pulmonary Vascular Disease Phenomentioning
confidence: 99%